A new genus of the subfamily Nemobiinae (Orthoptera: Gryllidae) with unclear tribal position for a new species from Madagascar - Gorochov, Andrei V. (Zootaxa, 2025)
The genus Storozhenkoa gen. nov. and its type species S. sergeyi sp. nov. are described from Madagascar. This monotypic genus belongs to the subfamily Nemobiinae, but its tribal position is unclear. The new genus is characterized by a spotted body coloration, rather long legs with only inner tympana, short dorsal spines of the hind tibia, the absence of one of apical spurs on this tibia, well developed but shortened male tegmina with a characteristic structure of their stridulatory apparatus, the male genitalia with long endoparameral apodemes, and a long ovipositor with a simple and acute apical part.